2012
DOI: 10.1039/c2ra20514a
|View full text |Cite
|
Sign up to set email alerts
|

DEMS-monitoring liquid | gas interfacial ammonia oxidation at carbon nanofibre membranes

Abstract: Electrochemical ammonia oxidation is of interest in waste treatment as well as in electrochemical sensing applications and demonstrated here at a carbon nanofibre (''bucky-paper'') electrode. The electrode is placed at the aqueous electrolyte | gas interface, and current (cyclic voltammetry) as well as ambient differential electrochemical mass spectrometry (DEMS, cyclic voltbarometry) data are recorded as a function of solution composition and pH. The oxidation of oxalate to CO 2 is employed as a test and cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It cannot be excluded that NO and N 2 O were formed, as was found at BDD (Michels et al, 2010). However, it was demonstrated that the main gaseous nitrogen product from direct ammonia oxidation is molecular nitrogen (Webster et al, 2012;Michels et al, 2010). Thus, it is very likely that N 2 was the main gaseous nitrogen compound in our experiments.…”
Section: Direct Ammonia Oxidation As a Treatment Process For Stored Umentioning
confidence: 55%
See 1 more Smart Citation
“…It cannot be excluded that NO and N 2 O were formed, as was found at BDD (Michels et al, 2010). However, it was demonstrated that the main gaseous nitrogen product from direct ammonia oxidation is molecular nitrogen (Webster et al, 2012;Michels et al, 2010). Thus, it is very likely that N 2 was the main gaseous nitrogen compound in our experiments.…”
Section: Direct Ammonia Oxidation As a Treatment Process For Stored Umentioning
confidence: 55%
“…Since the total charge was 1.65 Ah, the mineralization of graphite could account for about one third of the anodic current. The competition of direct ammonia oxidation, CO 2 formation and oxygen evolution on carbon fibers was pointed out by Webster et al (2012). The low current efficiency for ammonia oxidation therefore most probably resulted from a combination of organics oxidation, graphite mineralization and oxygen evolution.…”
Section: Activity and Selectivity Of Graphite For Direct Ammonia Oxidmentioning
confidence: 99%
“…37 Indeed, scanning to a potential of +1.3 V has been shown to etch the carbon surface at a rate of 0.24 nm/min (~70 femtometer/voltammogram), 26 presumably by way of carbon dioxide generation at the electrode surface. 103…”
Section: Fscv: Under Construction…mentioning
confidence: 99%
“…Carbon nanofibers provide robust but highly porous films with high surface area and convenient synthesis often based on bio‐resources . They are readily obtained with negative surface charge and deposited from suspension into mechanically robust porous films . Carbon nanofibers (CNFs) represent a class of carbon nanomaterials with a fibrous (and sometimes tube‐like) structure that is relatively cheap and easy to synthesize .…”
Section: Introductionmentioning
confidence: 99%
“…[26] They are readily obtained with negative surface charge and deposited from suspension into mechanically robust porous films. [27] Carbon nanofibers (CNFs) represent a class of carbon nanomaterials with a fibrous (and sometimes tube-like) structure that is relatively cheap and easy to synthesize. [28] A common synthetic route to CNFs is based on electrospinning of polymer solutions (e. g. poly-acrylonitrile or poly-pyrrole in an organic solvent such as DMF) followed by carbonization in the presence of inert gas.…”
Section: Introductionmentioning
confidence: 99%